Translating culture: the rise and resonance of Chinese contemporary literature in the Portuguese-speaking world - Xin Huang; Xiang Zhang (Humanities & Social Sciences Communications)
Abstract The article provides an overview of the translation and reception of contemporary Chinese literature in the Portuguese-speaking world, shedding light on the dynamics of cross-cultural literary exchange and reader engagement. It presents the extent, diversity, and marketing ratio of Chinese literary works translated into Portuguese, and utilizes this information to investigate how Portuguese-speaking readers engage with these translated works, focusing on their preferences, interests, demographics, and the impact of linguistic backgrounds. It then analyzes the reviews of well-received translations, including the Three-Body Problem trilogy, Iron Widow, and The Good Women of China, to determine how Portuguese-speaking readers interpret Chinese elements, historical references, narrative styles, and themes. The findings indicate the formation of the overarching impression of the ‘Chinese’ image among Portuguese-speaking readers and the potential development of the stereotypical views of Chinese women. Additionally, the study reveals that the exploration of fantasy as a universal passion underscores shared experiences that transcends cultural boundaries, connecting readers in China to those in the Portuguese-speaking world. The study highlights the challenges faced by Portuguese-speaking readers in understanding the intricacies of Chinese contexts, emphasizing the need for more detailed depiction and contextual understanding of translations. The article concludes by calling for further research on translation strategies, reader engagement, and shifts within literary systems to enhance cross-cultural literary exchange.